Best Answer

The answer to 3 plus X plus -7 times 6 equals-38. This is considered to be a math problem.

Q: 3 plus x plus -7 x 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(-7 x -3) + (-6) = 21 - 6 = 15

x = -6 x/-3 + 5 = 7 x/-3 = 2 x = -6

The answer to the equation 3 2x-4 plus 2 x plus 7 6 is 34x + 72.

The patterns is formed from the product of the first number and the absolute difference of the two numbers. 1 x l4 - 1l = 1 x 3 = 3 3 x l7 - 3l = 3 x 4 = 12 6 x l5 - 6l = 6 x 1 = 6 7 x l10 - 7l = 7 x 3 = 21 11 x l7 - 11l = 11 x 4 = 44

Solve for x. 3x + 3 = x + 7 2x + 3 = 7 2x = 4 x = 2 Check it. 6 + 3 = 2 + 7 It checks.

Related questions

(-7 x -3) + (-6) = 21 - 6 = 15

3 times 7 plus 6 is equal to 27.

x = -6 x/-3 + 5 = 7 x/-3 = 2 x = -6

The answer to the equation 3 2x-4 plus 2 x plus 7 6 is 34x + 72.

x2+x-6 = (x-2)(x+3) when factored

The patterns is formed from the product of the first number and the absolute difference of the two numbers. 1 x l4 - 1l = 1 x 3 = 3 3 x l7 - 3l = 3 x 4 = 12 6 x l5 - 6l = 6 x 1 = 6 7 x l10 - 7l = 7 x 3 = 21 11 x l7 - 11l = 11 x 4 = 44

Solve for x. 3x + 3 = x + 7 2x + 3 = 7 2x = 4 x = 2 Check it. 6 + 3 = 2 + 7 It checks.

3 x 2 + x = -7 >> 6 + X = -7 >>> x = -13

25x+1=33x+7 25x=33x+6 -8x=6 x=-8/6 x=-4/3

6 + (3 x 7) - 2 = 25

-7 + 2(x-3) = -7+2x-6 = 2x - 13

3x + 7 = -3x 6x = -7 x = -7/6